(x-1)(x+3)=(x+2)(x-3)

Simple and best practice solution for (x-1)(x+3)=(x+2)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(x+3)=(x+2)(x-3) equation:


Simplifying
(x + -1)(x + 3) = (x + 2)(x + -3)

Reorder the terms:
(-1 + x)(x + 3) = (x + 2)(x + -3)

Reorder the terms:
(-1 + x)(3 + x) = (x + 2)(x + -3)

Multiply (-1 + x) * (3 + x)
(-1(3 + x) + x(3 + x)) = (x + 2)(x + -3)
((3 * -1 + x * -1) + x(3 + x)) = (x + 2)(x + -3)
((-3 + -1x) + x(3 + x)) = (x + 2)(x + -3)
(-3 + -1x + (3 * x + x * x)) = (x + 2)(x + -3)
(-3 + -1x + (3x + x2)) = (x + 2)(x + -3)

Combine like terms: -1x + 3x = 2x
(-3 + 2x + x2) = (x + 2)(x + -3)

Reorder the terms:
-3 + 2x + x2 = (2 + x)(x + -3)

Reorder the terms:
-3 + 2x + x2 = (2 + x)(-3 + x)

Multiply (2 + x) * (-3 + x)
-3 + 2x + x2 = (2(-3 + x) + x(-3 + x))
-3 + 2x + x2 = ((-3 * 2 + x * 2) + x(-3 + x))
-3 + 2x + x2 = ((-6 + 2x) + x(-3 + x))
-3 + 2x + x2 = (-6 + 2x + (-3 * x + x * x))
-3 + 2x + x2 = (-6 + 2x + (-3x + x2))

Combine like terms: 2x + -3x = -1x
-3 + 2x + x2 = (-6 + -1x + x2)

Add '-1x2' to each side of the equation.
-3 + 2x + x2 + -1x2 = -6 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-3 + 2x + 0 = -6 + -1x + x2 + -1x2
-3 + 2x = -6 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-3 + 2x = -6 + -1x + 0
-3 + 2x = -6 + -1x

Solving
-3 + 2x = -6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-3 + 2x + x = -6 + -1x + x

Combine like terms: 2x + x = 3x
-3 + 3x = -6 + -1x + x

Combine like terms: -1x + x = 0
-3 + 3x = -6 + 0
-3 + 3x = -6

Add '3' to each side of the equation.
-3 + 3 + 3x = -6 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = -6 + 3
3x = -6 + 3

Combine like terms: -6 + 3 = -3
3x = -3

Divide each side by '3'.
x = -1

Simplifying
x = -1

See similar equations:

| -2*x+8=-16 | | -3x+4y=46 | | 5y-7y-6=2 | | 14=7p-ap | | 6x-6=-216 | | -6*x=42 | | 6x-4+5x=-26 | | 7y-2=6y^2 | | 5m^2-85m=0 | | x^2-17x+70=10 | | 4c^2+12x-44=0 | | 16x^2-9y^2+36y+108=0 | | Y=(-3)(4i)(7i) | | 7x-(4x+3)=1 | | [3y-2]=[26-4y] | | 16y-6=2 | | -x+9-9= | | 121x^2-16=-7 | | T*23=276 | | y=-4.9t^2+26t | | 38+2d=100 | | 82(2)= | | 4x-9.8=4.6 | | n^2+4n-3=9 | | 180-81= | | k^2+14k-54=-3 | | .1(x+1000)-.06=260 | | A=91-2x | | on(x+4)-ln(x+1)=lnx | | 16y+7=19 | | 25x^2-30x+4=0 | | 7+x-9= |

Equations solver categories